Achievement of Adolescent Development, Self Identity and Knowledge about the Dangers of Drug Abuse and Free Sex Through Health Education and Therapeutic Group Therapy - Zakiyah Zakiyah; Aan Sutandi; Harizza Pertiwi (Alma Ata University Press, 2020)
Adolescents whose identities have been reached tend to be more autonomous and creative, they also show a greater capacity to establish intimacy. On the other hand, if the process of achieving self-identity is experiencing obstacles, it can cause identity confusion. They can also experience various problems and have risky behaviors such as drug abuse and free sex. Of this study is to improve the ability of adolescents to achieve their development, identity, and to increase adolescent knowledge about the dangers of drug abuse and free sex. Used was quasi-experimental with pretest-posttest using purposive sampling technique on 21 teenagers at 49 Junior High School, Kramat Jati, East Jakarta . Of the study are: (1) level of knowledge before and after intervention is obtained (6.76 ± 1.51 to 8.62 ± 1.59); (2) adolescent development before and after the intervention (42.57 ± 10.3 to 42 , 71 ± 2.95) with a significance level of 0.94 (t-test); (3) adolescent identity before and after the intervention (79.14 ± 13.41 - 86.43 ± 10.35) with a significance level of 0.01 (t-test). Based on the results of the study, it was concluded that there is no relationship between adolescent Therapeutic Group Therapy (TGT) with adolescent development, and there is a relationship between adolescent TGT and health education on identity and knowledge about the dangers of drug abuse and free sex.